HYDROLOGICAL, SOIL AND MICROCLIMATE POTENTIAL ON THE TERRITORY OF PANČEVO IN FUNCTION OF AGRICULTURAL PRODUCTION - Kljajić, Nataša; Vuković, Predrag; Roljević, Svetlana (Economics of Agriculture, 2011)
The climate is the result of work done by complex climatic systems and it affects the overall development of agriculture and society of a certain area. Climatic elements possess natural variability which can be found out in two ways: directly, using the meteorological measurements and indirectly, applying some other methods. Agricultural production of a certain area largely depends on its productive capability and the way of being used. The mere facts that the tissue of all living forms on Earth consists of 50 – 80 % of water and that all vital activities are done in the interiority of a living organism, speaks enough about the importance of water as a natural source of life. Regarding this, this paper analyses climatic parameters, pedological characteristics and water potentials in the function of evaluation of the specificity of this agricultural area concerning these characteristics and their influence on agriculture. Using the available data of "Tamis" Institute, The Republic Hydrometeorological Service, Statistical Office of the Republic of Serbia, and the internal data of the municipality of Pancevo, the general conclusion is that this area is characterized by favourable climatic parameters , quality soil of high productive capability and quite favourable water resources. The conditions are favourable for an intensive and profitable agricultural production; therefore, the development of this area should be directed towards intensifying agricultural production by introducing complex agrotechnical and hydromeliorative measures.